Do High-Income or Low-Income Immigrants Leave Faster? - Govert Bijwaard; Jackline Wahba (Institute for the Study of Labor (IZA), 2013)
We estimate the impact of the income earned in the host country on return migration of labor migrants from developing countries. We use a three-state correlated competing risks model to account for the strong dependence of labor market status and the income earned. Our analysis is based on administrative panel data of recent labor immigrants from developing countries to the Netherlands. The empirical results show that intensities of return migration are U-shaped with respect to migrants' income, implying a higher intensity in low- and high- income groups. Indeed, the lowest-income group has the highest probability of return. We also find that ignoring the interdependence of labor market status and the income earned leads to an overestimating the income effect on departure.
Keywords: F22; J61; C41; 330; migration dynamics; labour market transitions; competing risks; immigrant assimilation